Low irradiance compared with conventional photodynamic therapy in the treatment of actinic keratoses - Gholam, Patrick; Bosselmann, Ina; Enk, Alexander; Dick, Julika (Photodermatology, photoimmunology & photomedicine, 2019)
Background: Photodynamic therapy (PDT) is an effective therapy treating photodamaged areas with multiple actinic keratoses (AK). Still pain during therapy is one of the most challenging obstacles for patients. This retrospective study compares pain and efficacy intra-individual in patients using conventional PDT (c-PDT) compared to a low irradiance PDT protocol (li-PDT) with a reduced irradiance to 25% of c-PDT. Methods: Thirty-one patients were enrolled into this retrospective analysis treated with li-PDT and c-PDT on comparable fields of actinic damage on the forehead or the cheek. Pain was scored by the patients using a VAS. Moreover, number and time to therapy interruptions were documented. For effectiveness number and grade of AK were counted before and 4 weeks after PDT. Results: Maintaining a total light dose of 37 J/cm2, a decrease in irradiation in li-PDT patients resulted in significant less pain (VAS score 2.8 vs 7.6) and fewer therapy interruptions compared to treatment with c- PDT (P < 0.0005). No significant difference in treatment outcome was found (P = 0.068). Conclusion: Our data shows that li-PDT can reduce pain with at least comparable clinical outcome compared to c-PDT. Therefore, it is an effective and well-tolerated treatment for patients with multiple AK.
First published: 05 October 2018
Gesehen am 05.04.2019